Política de permanência universitária: Bolsa Auxílio Especial aos estudantes da Universidade Estadual de Feira de Santana, no período 2014 a 2018 - Evangelista, Wildacy Gonçalves Ribeiro (2021)
The Permanence Policies practiced by the State or by the Public Institutions of Higher Education do not support the number of students who demand specific, material and symbolic actions, to provide the academic journey. Referring to this problem, this dissertation presents a study of the Bolsa Auxílio Especial Program, developed by the State University of Feira de Santana until 2018 when it was replaced by Resident Aid, with the main objective of analyzing the obstacles and challenges of the Permanence Policy the University in granting the aforementioned scholarship and the effectiveness of the action with the beneficiaries, taking as a reference the look and feeling of those who lived the experience of being or not included in the program. For this, methodological procedures based on qualitative research, semi-structured interviews, questionnaires and documentary analysis were used as data collection instruments. The results found reveal that the program, in force for twenty-three years, was essential for the permanence of the students participating in the research until the conclusion of the graduation, even considering the financial and operational problems that have affected it since its implementation. It was also possible to identify the main difficulties of the researched students, as well as the weaknesses of the University in the process of elaboration and execution of Permanence Policies. The democratization of access promoted by the State University of Feira de Santana, which started five years before the implementation of the Quota Law, as well as in other institutions of higher education in the country, is not proportional to the student population in a situation of socioeconomic vulnerability, a reality that is explicit that permanence policies need to be redesigned if they are to be truly inclusive. The access promoted by the University entitles it as inclusive, but the actions developed in its Permanence Policy, such as the Bolsa Auxílio Especial Program, for not reaching the totality of students in need of assistance, characterize it as exclusionary, since insertion in the programs is through selections with socioeconomic assessments.